Within-city Spatial Variations in Ambient Ultrafine Particle Concentrations and Incident Brain Tumors in Adults. Issue 2 (March 2020) - Weichenthal, Scott; Olaniyan, Toyib; Christidis, Tanya; Lavigne, Eric; Hatzopoulou, Marianne; Van Ryswyk, Keith; Tjepkema, Michael; Burnett, Rick
Abstract : Background: Ambient ultrafine particles (UFPs, <0.1 µm) can reach the human brain, but to our knowledge, epidemiologic studies have yet to evaluate the relation between UFPs and incident brain tumors. Methods: We conducted a cohort study of within-city spatial variations in ambient UFPs across Montreal and Toronto, Canada, among 1.9 million adults included in multiple cycles of the Canadian Census Health and Environment Cohorts (1991, 1996, 2001, and 2006). UFP exposures (3-year moving averages) were assigned to residential locations using land-use regression models with exposures updated to account for residential mobility within and between cities. We followed cohort members for malignant brain tumors (ICD-10 codes C71.0–C71.9) between 2001 and 2016; Cox proportional hazards models (stratified by age, sex, immigration status, and census cycle) were used to estimate hazard ratios (HRs) adjusting for fine particle mass concentrations (PM2.5 ), nitrogen dioxide (NO2 ), and various sociodemographic factors. Results: In total, we identified 1, 400 incident brain tumors during the follow-up period. Each 10, 000/cm 3 increase in UFPs was positively associated with brain tumor incidence (HR = 1.112, 95% CI = 1.042, 1.188) after adjusting for PM2.5, NO2, and sociodemographic factors. Applying an indirect adjustment for cigarette smoking and body mass index strengthened this relation (HR = 1.133, 95% CI = 1.032, 1.245). PM2.5 and NO2 were not associated with an increased incidence of brain tumors. Conclusions: Ambient UFPs may represent a previously unrecognized risk factor for incident brain tumors in adults. Future studies should aim to replicate these results given the high prevalence of UFP exposures in urban areas. Abstract : Supplemental Digital Content is available in the text.